Correlation of Clinical Score and Serum Acetylcholinesterase Level as a Predictor of Outcome among Patients with Acute Organophosphate Poisoning Admitted in Emergency Ward of a Tertiary Hospital - Chaudhary, R; Bhandari, R; Malla, G; Poudel, M.; Lamsal, M (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Monitoring a patient's serum acetylcholinesterase (AChE) status after clinical score of organophosphate poisoning enables the verification of exposure to anticholinesterase agents.Methods: A cross-sectional study was conducted among the patients fulfilling the inclusion criteria and was categorized according to POP (Peradeniya Organophosphorus Poisoning) score. The study was conducted at a tertiary hospital for one year in the period of Jan 2016 to Dec 2016. POP score was applied and serum acetylcholinesterase level was determined in the lab. Spearman’s rho coefficient method was applied for correlation.Results: Seventy four patients survived in emergency ward who presented within (4.1 ± 2.9; 95% confidence interval [CI], 3.43- 4.80; P= 0.021) hours of ingestion of OP compounds, POP score 3 (Q1, Q3, 2, 4), serum AChE 2221 (Q1, Q3, 768.5, 4703.5) IU/L with 9 ( Q1,Q3, 8.75, 34.75) mg of atropine used, 94% received PAM for 5 (Q1, Q3, 3, 7) days of hospital stay.Four patients died within (7.5 ± 5.4; 95% CI, -1.16- 16.16; P= 0.021) hours of presentation, POP score of 4 (Q1, Q3, 4, 7.75), serum AChE 588 (Q1, Q3, 173, 1912) IU/L, atropine used 170 (Q1, Q3, 152.5, 297) mg, 5.1% received PAM for 3.5 (Q1, Q3, 1, 11.25) days of hospital stay.Spearman’s rho coefficient showed well correlation between POP score and serum AChE level (coefficient -0.356; P= 0.001), POP score for the need of atropine (coefficient= 0.536; P= 0.001).Serum AChE also correlated with the length of hospital stay (coefficient= 0.414; P= 0.001) compared to POP score (coefficient= 0.420; P= 0.001).Conclusions: The higher degree of POP score correlated to higher degree of serum acetylcholinesterase derangement, need for atropine, PAM and length of hospital stay. Thus, it enhances in the prediction of outcome among patients with acute organophosphate poisoning at index visit.